The Development of English Literature for Tenth Grade Students - Ahmad Syaufan Muttaqi (Graduate Program, University of Islam Malang, 2019)
AbstractThis research is conducted to answer the lack of teaching materials on the textbooks for both the teachers and students use; the book has tittle ‘’Language and English Literature for the 10th grade’’ and it used in MAN 1 Nganjuk. The development here focused on developing English literature material. The English literature material explained on the product was about the kind of literary work. The product designed here was the English literature for the basic level. The product presented the introduction and explanation of the literary work for the basic level. This product gave the additional material to help the teacher and students in the learning and teaching process, especially in English literature subject. In the previous textbook, the English literature material only contains about Song lyric and Proverb. According to the teachers, it is not able to accomplish the learning of English literature purpose. In this research, the researcher did the needs analysis to identify the problems, then proceed with the product's development; begin with deciding the title for each unit and the material, and also give some pictures and exercises. The validation is done and obtains some feedback for some revision before the tryout to the small group of the students. This product was better than the previous, it was because sometimes the book does not give a clear example and even without the explanation, which can be the problem for students. So, then this book focused on how the student can understand the material presented, so the aim of learning English literature can be achieved by the students. Key Words: English Literature material, Tenth-grade students